INOVASI APLIKASI SAWIT RAKYAT ONLINE PROVINSI RIAU (STUDI KASUS DAMPAK APLIKASI TERHADAP PETANI SWADAYA) - zuhdi, Albari; Nailul Fauziah; Annisa Ramanda Putri (Jurnal Ilmu Administrasi Negara, 2024)
The widespread availability of fake oil palm seeds is a problem for farmers. To overcome this problem, the Sawit Rakyat Online (SRO) application is present. This application is a form of digitization carried out by a state-owned plantation company, PT. Nusantara Plantation V (PTPN V). The purpose of this study is to provide information to farmers in accessing and obtaining certified superior oil palm seeds, as well as providing information on how to buy legal oil palm seeds and avoid fraud. Thus, the Sawit Rakyat Online (SRO) application aims to increase palm oil productivity and overcome the problem of fake palm seeds that are an obstacle for oil palm farmers. As well as increasing the contribution of the palm oil industry to the national and global economy. This research uses qualitative methods with a type of data analysis in the form of descriptive. The results showed that this application runs well, proven by the positive assessment from the users. However, there are some shortcomings contained in this application and need to be evaluated and improved. Therefore, PTPN V needs to improve access to farmer services via digital and evaluate the capabilities of application features.